Analisis Konsistensi Laporan Neraca pada Laporan Keuangan Pemerintahan Kota Medan 2020-2023 - Agape Anjumarito Panjaitan; Gloria Sthefany; Muhammad Rizal (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
Consistency in the presentation of financial statements is an important factor to ensure transparency, accountability and comparability of information in the long term. Consistency ensures that the final financial statements are reliable, relevant and comparable. This principle is based on uniform recording procedures in recording similar transactions in a standardized way, so as to maintain accurate and informative financial records.This study aims to analyze the consistency of the balance sheet report in the Medan City Government Financial Report during the 2020-2023 period. The research method used is documentation analysis of the balance sheet reports from 2020 to 2023 with year-to-year comparison techniques and evaluation of the variability of recording assets, liabilities, and equity. In addition, a qualitative approach through interviews with relevant parties is used to understand the factors that influence reporting consistency. The results show that there is variability in the presentation of balance sheet reports that can be caused by changes in accounting policies, the application of Government Accounting Standards (SAP), and administrative factors. Therefore, a stricter application of accounting standards is needed to maintain the consistency and quality of financial statements.